Destilação para tratamento de lixiviado : obtenção de subsídios para projeto e avaliação - Cândido, Everton da Silva (2021)
The landfill leachate, due to the high pollutant load and complex composition, is one of the main sources of environmental contamination. In order to minimize impacts and achieve the requirements of environmental legislation, it is necessary to treat the leachate before launching it into water bodies. In this scenario, solar distillation is a treatment process indicated for regions such as Mato Grosso, with favorable climatic conditions, with a warmer and drier climate. Thus, this work aims to design, build and evaluate the leachate treatment system, by natural and forced evaporation, using a pilot scale solar distiller. The methodology consists in the following steps: i) testing and analyzing the materials (galvanized steel, stainless steel, aluminum, glass and acrylic); ii) analysis of the interference of climatic conditions in the solar distillation of the leachate; iii) determination of the average daily leachate evaporation (L/d) in a system with natural distillation and forced distillation; and iv) evaluate the distilled effluent in accordance with current legislation. According to the results, stainless steel performed better for building the base of the distiller, with less loss of mass, with an average result of 0.03%, and a lower corrosion rate, equaling 0.00054. For the cover of the distiller, the glass presented the best result. In the monitoring of climatic conditions, it was found that, in natural distillation, there was a decrease in production in the rainy season, when there was less solar radiation and precipitation. The forced distillation was not influenced by climatic conditions. Forced distillation achieved a production of 84 L/day and, natural distillation, 12 L/day. The rates of removal of the analyzed parameters are lower than those established by current legislation.